2012
DOI: 10.6061/clinics/2012(05)02
|View full text |Cite
|
Sign up to set email alerts
|

Current practices in the management of patients with ureteral calculi in the emergency room of a university hospital

Abstract: OBJECTIVE:Urinary lithiasis is a common disease. The aim of the present study is to assess the knowledge regarding the diagnosis, treatment and recommendations given to patients with ureteral colic by professionals of an academic hospital.MATERIALS AND METHODS:Sixty-five physicians were interviewed about previous experience with guidelines regarding ureteral colic and how they manage patients with ureteral colic in regards to diagnosis, treatment and the information provided to the patients.RESULTS:Thirty-six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Many theories, such as the gate control theory of pain, severe stimulation, inhibition of stimulation of the nerves transferring the pain, distracting the senses, and controlling the release of inhibitors, may focus on the release of internal opioids. [1617] The endorphin terminals of the pain can be found in the hypothalamus and pituitary gland can be found while stimulating. Observations have shown that injection of naloxone inhibits the effects of normal saline,[1213] and perhaps this issue shows that normal saline transmits pain to the brain through the nerves, and then alleviates pain by releasing internal opioids.…”
Section: Discussionmentioning
confidence: 99%
“…Many theories, such as the gate control theory of pain, severe stimulation, inhibition of stimulation of the nerves transferring the pain, distracting the senses, and controlling the release of inhibitors, may focus on the release of internal opioids. [1617] The endorphin terminals of the pain can be found in the hypothalamus and pituitary gland can be found while stimulating. Observations have shown that injection of naloxone inhibits the effects of normal saline,[1213] and perhaps this issue shows that normal saline transmits pain to the brain through the nerves, and then alleviates pain by releasing internal opioids.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dipyrone has been banned in the USA and certain European countries for allegedly causing agranulocytosis in the bone marrow and fluid/electrolyte imbalance (2). However, in numerous countries, it is still frequently prescribed in neurosurgery clinics (3) or is administered systemically in emergency departments (4). Long-term use of dipyrone loses efficacy to analgesic effects; this has been identified in the last few years as an important problem (1).…”
Section: Introductionmentioning
confidence: 99%
“… 3 5 The prevalence of urinary stones in RC is 10%–15%. 6 Pain experienced in the acute phase of RC is often described as “the worst pain ever”, 7 making effective pain control a priority in RC management. Currently, analgesics represent the mainstay treatment for this condition, and for many years, opioids have been used as first-line treatment.…”
Section: Introductionmentioning
confidence: 99%